Kajian Penerapan Ekowisata di Kawasan Pariwisata Padangbai Bali - Harimurti, I Gede; Acwin Dwijendra, Ngakan Ketut (Media Wisata, 2022)
Study of eco-tourism application In the coastal area, Padangbai Village, Bali. Ecotourism is an environmental-based industrial activity that seeks to reduce the impact that appears on nature and local culture while creating job opportunities increasing income and helping nature itself. The Padangbai tourism area has tourism potential, namely Padangbai Beach and the Silayukti Temple Area, which are both locations is side by side but with different activities so far they are running harmoniously. This is interesting for the author to examine the extent to which these two tourism objects apply the concept of ecotourism. This study uses a descriptive qualitative method with a case study approach by assessing ecotourism indicators. The results of this study are the principles in the concept of ecotourism have been fulfilled in aspects of environmental conservation, cultural education, and community participation. Parameters that show the strength of the application of ecotourism and the emphasis is more on the eco-religious aspect.